Gender Role Discrepancy, Discrepancy Stress, and Family Resilience of Minangkabau Family - Mukhlisah, Nurul; Pudjiati, Sri Redatin Retno (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2021)
Family resilience is an important ability for family in facing various challenges throughout the lifespan. The study about family resilience of Minangkabau ethnic people needs further exploration due to the increase in divorce rate in the last three years, indicating that these families were not resilient. The cause of the divorce was related to matrilocal residency (husband lives in wife’s house after marriage). This residency has the potential to cause the intervention of the wife’s family to the relationship of husband and wife, therefore leading to the lack of authority in the husband's role. This condition poses a risk to husbands to experience gender role discrepancy and discrepancy stress. The purpose of this study was to examine the contribution of gender role discrepancy and discrepancy stress to family resilience by involving 139 Minangkabau men who lived in the wife’s family house around the age 18-50 years old. This study used a quantitative research method. Sampling technique used in this study was a purposive sampling technique. All data collected were analyzed by using multiple regression method. Results showed that gender role discrepancy and discrepancy stress contributed significantly to family resilience by 10.5%. However, partial analysis showed that discrepancy stress alone did not contribute significantly to family resilience.